Pengaruh pendidikan kesehatan dengan media video terhadapa peningkatan pemgetahuan tentang bahaya merokok pada siswa di SMK Mathlaul Huda Kabupaten Tangerang tahun 2023 - Kardi, Kardi; Karim, Abdul; Bage, Libertus (Yayasan Pusat Pendidikan Vanchapo, 2023)
Smoking is a habit that can be found in almost every society. Around the world, 7.1 million people died from smoking in 2016, including 5.1 million men and 2 million women. That is, smoking causes one death every five seconds. Along with the rate of smoking, this death rate will continue to increase. Smoking rates among men are generally higher than among women. The World Health Organization notes that currently 36% of Indonesia's population smokes, or more than 60 million people. Research Objectives. To determine the effect of health education using video media on the level of knowledge about the dangers of smoking in students at SMK Mathlaul Huda, Tangerang district, in 2023. Methods. analytic survey research with a Quasi Experiment design one group pre and post test. The sample in this study totaled 138 people and the sampling technique used was total sampling technique. The research data used primary data by filling out questionnaires. The collected data was then processed computerized .Results. Prior to health education, 60 people (50.4%) had enough knowledge about the dangers of smoking, both 49 people (41.2%) and less, 10 people (8.4%) and were categorized as . After health education, 114 people (95.8%) had good knowledge about the dangers of smoking, and a minority of respondents who had sufficient knowledge were 5 people (4.2%). Conclusion. This study shows that there is an influence between before and after being given health education, this is evidenced by the acquisition of statistical test results which show a p-value of 0.000 α 0.05, which means that there is a significant effect between before and after being given health education to students of SMK Mathlaul Huda, Tangerang district.